2013
DOI: 10.1111/jmg.12029
|View full text |Cite
|
Sign up to set email alerts
|

Trace element composition of continentally subducted slab‐derived melt: insight from multiphase solid inclusions in ultrahigh‐pressure eclogite in the Dabie orogen

Abstract: The ultrahigh-pressure (UHP) eclogite in the Dabie orogen preserves petrological evidence for the existence of hydrous silicate melts that formed during continental subduction-zone metamorphism. This is indicated by occurrence of multiphase solid (MS) inclusions in garnet that primarily consist of K-feldspar + quartz AE epidote/allanite. All the MS inclusions are euhedral to subhedral in morphology and surrounded with radial cracks in the host garnet. Their trace element compositions were analysed by two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 85 publications
4
59
0
2
Order By: Relevance
“…Thus, trace element characteristics of Kfs+Qz inclusions are similar to those of granitic melt [27], suggesting that these melt likely derived from trapped melt that was produced during incongruent phengite melting. It is consistent with a previous investigation [28]. However, field observations showed that melting of host eclogite is very limited.…”
Section: The Low-degree Partial Melting Of Uhp Eclogite: Evidence Frosupporting
confidence: 82%
“…Thus, trace element characteristics of Kfs+Qz inclusions are similar to those of granitic melt [27], suggesting that these melt likely derived from trapped melt that was produced during incongruent phengite melting. It is consistent with a previous investigation [28]. However, field observations showed that melting of host eclogite is very limited.…”
Section: The Low-degree Partial Melting Of Uhp Eclogite: Evidence Frosupporting
confidence: 82%
“…This has been observed in many UHP metamorphic rocks where anatexis takes place at relatively high temperatures due to breakdown of hydrous UHP minerals such as phengite during decompression (Gao et al 2012(Gao et al , 2013Chen et al 2013;Liu et al 2013). In a series of experiments on the rheology of eclogite at 1,300 to 1,500 K and 3.0 GPa, on the other hand, Zhang et al (2004) observed partial melting of an eclogite that contained no hydrous minerals but only H 2 O of up to 300 ppm in garnet, 1,000 to 1,300 ppm in omphacite and 3,000 to 4,000 ppm in rutile.…”
Section: Water In Subduction-zone Rocksmentioning
confidence: 99%
“…The liberated water may result in the formation of retrograde hydrous minerals in UHP rocks . If exhumation occurs at elevated temperatures, the hydrous UHP minerals such as phengite may break down during decompression, resulting in local anatexis of the UHP rocks (Gao et al 2012(Gao et al , 2013Chen et al 2013;Liu et al 2013).…”
Section: Water In Subduction-zone Rocksmentioning
confidence: 99%
See 2 more Smart Citations